2020
DOI: 10.1002/bsd2.101
|View full text |Cite
|
Sign up to set email alerts
|

Regional financial integration and its impact on banking development: Evidence from Southern African Development Community countries

Abstract: The study investigated the impact of regional financial integration on banking sector development with specific focus on the impact of the Southern African Development Community protocols on trade and finance and investment. A total of 14 countries made up the study sample, and the panel cointegration fully modified ordinary least squares model (FMOLS) alongside the generalized method of moments (GMM) were used to estimate the nature of the impact. Study findings showed that regional integration through the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
2
1
0
Order By: Relevance
“…Results of Kao (1999) OPEN 1, OPEN 2 and OPEN 3 stands for trade openness as measured by total trade (% of GDP), total exports of goods and services (% of GDP) and total imports of goods and services (% of GDP) respectively. The panel co-integration results show that a null hypothesis which states that there exists a long run relationship between the variables under study cannot be rejected at 1 percent significance level, in line with Tembo (2018). Similar results were also found by similar empirical research done by Osei et al (2019), Mbogela (2019) and Tahir et al (2018).…”
Section: Panel Co-integration Testssupporting
confidence: 84%
“…Results of Kao (1999) OPEN 1, OPEN 2 and OPEN 3 stands for trade openness as measured by total trade (% of GDP), total exports of goods and services (% of GDP) and total imports of goods and services (% of GDP) respectively. The panel co-integration results show that a null hypothesis which states that there exists a long run relationship between the variables under study cannot be rejected at 1 percent significance level, in line with Tembo (2018). Similar results were also found by similar empirical research done by Osei et al (2019), Mbogela (2019) and Tahir et al (2018).…”
Section: Panel Co-integration Testssupporting
confidence: 84%
“…Unlike at level, all variables used are integrated of order 1 at first difference. These results paved way for panel co-integration tests to be undertaken, consistent with Tembo (2018).…”
Section: Correlation Analysissupporting
confidence: 72%
“…Investors might benefit from opportunities in various economies and locations that may have varying economic cycles or growth prospects by diversifying their holdings geographically (Miah et al, 2023). Furthermore, research has indicated that geographic diversification can provide a more stable portfolio and lower volatility over the long term, both of which can increase risk‐adjusted returns (Tembo & Makina, 2020; Wulansari & Adhariani, 2023). By combining diversification strategies, managers may be able to better manage the complexity and diversity created by each strategy.…”
Section: Introductionmentioning
confidence: 99%